South Koreans’ responses to evolution and creationism: a survey and its implications - Park, Hyung Wook (2022)
I analyze the results of a survey on the public reception of evolution and creationism in South Korea. I reconfirm findings from previous studies, which demonstrated the significance of antievolutionism in the country. The proportion of Koreans who deny or are skeptical toward evolution constitutes 31.6 percent of the population. They tend to be Protestants, women, seniors, political conservatives, and from rural regions. I also report several seemingly anomalous findings. Notably, many respondents who professed no religion take the creationist stances. Moreover, young-earth creationism seems unpopular even among creationists, although it is the mainstream theory of the Korea Association for Creation Research, the country’s flagship creationist organization that influenced many Protestants. In contrast, the majority of the respondents, including evolutionists, endorse the creationist argument that both evolution and creationism should be taught in class. I provide my analyses and hypotheses on these results within Korea’s historical, religious, and cultural contexts.